1993
DOI: 10.1128/jb.175.3.674-683.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, nucleotide sequence, and expression of a gene encoding an adhesin subunit protein of Helicobacter pylori

Abstract: Gene hpaA, which codes for the receptor-binding subunit of the N-acetylneuraminyllactose-binding fibrillar hemagglutinin (NLBH) of Helicobacter pylori, was cloned and sequenced. The protein expressed by hpaA, designated HpaA, was identified as the adhesin subunit on the basis of its fetuin-binding activity and its reactivity with a polyclonal, monospecific rabbit serum prepared against NLBH purified from H. pylori. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis and Western blots (immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 48 publications
7
137
2
Order By: Relevance
“…H. pylori possesses several putative colonization factors, including flagella motility (Marshall & Warren, 1984), various adhesins (Evans et al, 1993;Falk et al, 1993;O'Toole et al, 1995), vacA (Salama et al, 2001) and urease (Marshall & Warren, 1984;Tsuda et al, 1994), some of which have been shown to be necessary for gastric colonization. Isogenic flaA 2 , flaB 2 and flaA flaB 2 mutant strains do not show full motility, and are unable to form effective colonies in the stomachs of germ-free piglets (Eaton et al, 1996).…”
Section: Implications Of Experimental Datamentioning
confidence: 99%
“…H. pylori possesses several putative colonization factors, including flagella motility (Marshall & Warren, 1984), various adhesins (Evans et al, 1993;Falk et al, 1993;O'Toole et al, 1995), vacA (Salama et al, 2001) and urease (Marshall & Warren, 1984;Tsuda et al, 1994), some of which have been shown to be necessary for gastric colonization. Isogenic flaA 2 , flaB 2 and flaA flaB 2 mutant strains do not show full motility, and are unable to form effective colonies in the stomachs of germ-free piglets (Eaton et al, 1996).…”
Section: Implications Of Experimental Datamentioning
confidence: 99%
“…A. Moore, B. Beckthold, S. Wong, A. Kureishi and L. E. Bryan, unpublished work (GenBank accession no. 29481) ; [45]q. Thus motifs A to C identified upstream of the H. pylori aroQ gene may also be potential promotors.…”
Section: Gene Signalsmentioning
confidence: 99%
“…Lewis b is commonly, but not universally, expressed on the surface of gastric epithelial cells (17). HpaA has been characterized as an N-acetylneuraminyllactose-binding hemagglutinin which is critical for mouse colonization (7,16). The HorB protein is paralogous with BabA, AlpA, and AlpB.…”
mentioning
confidence: 99%